Implementation of the Hela Tali Ecology Intelligence Tradition - Bety D.S Hetharion (Peneliti.net, 2020)
This study aims to determine the concept of the Ramkye Bhyea or Hela TaliTradition, and how the history of theTradition Ramkye Bhyea or Hela Tali in Masela District, Southwest Maluku Regency (MBD. This research method uses aapproach historical by trying to understand history and development.tradition Ramkye Bhyea in Serili Village, Marsela District, Southwest Maluku Regency in order to obtain accurate data The results showed that Ramkye byea is a tradition of fishing in the sea using young coconuttied to rattan or rope. leavesRamke Bhyea is known as a tradition because since 1946 when ramkye bhyea was introduced with the term pull the rope, it is still maintained and carried out every year in October